PEMBERIAN KONSELING GIZI DENGAN MEDIA BOOKLET TERHADAP PENGETAHUAN DAN SIKAP PASIEN DIABETES MELITUS - Sitti Kartika; Muhammad Dawam Jamil; Nugraheni Tri Lestari (JOURNAL HEALTH AND NUTRITIONS, 2023)
Diabetes mellitus is an important public health problem. Nutrition counseling for DM patients is the provision of education, understanding and training regarding knowledge and skills in DM diet management to each DM patient. Nutrition counseling is very necessary for changes in increasing knowledge. With good knowledge will affect a person's attitude, especially for people with DM. This knowledge will bring DM sufferers to determine their attitude. Therefore, the use of booklet media is an alternative to overcome the weaknesses that exist in leaflets. The purpose of research to know the effect of counseling with booklet media on knowledge and attitudes of people with diabetes mellitus. The methods of research was quasi-experimental research using a pre- test-post-test design with a control group. This research was conducted in February – May 2022. The population of this study were all inpatient DM patients at Penembahan Senopati Hospital, Bantul. Sampling by purposive sampling, each of which is 28 respondents for the booklet and leaflet group and the dependent variable the control and attitude of DM patients. Shapiro Wilk, Wilcoxon, and Mann Whitney data analysis.  The results of study was the difference between respondents before and after being given nutritional counseling with booklet and leaflet media there was a significant increase in knowledge and attitudes, namely knowledge in the booklet group (p = 0.001), attitudes (p = 0.000), and knowledge in the leaflet group (p = 0.017) and attitude (p=0.005). Booklets were more effective in increasing the knowledge (p=0.017) and attitudes (p=0.05) of DM patients compared to the use of leaflet media. The conclusion was used of booklet media is more effective than the use of leaflet media.Diabetes melitus adalah masalah kesehatan masyarakat yang penting. Konseling gizi pada pasien DM adalah pemberian pendidikan, pemahaman dan latihan mengenai pengetahuan dan keterampilan dalam penatalaksaan diet DM kepada setiap pasien DM. konseling gizi sangat diperlukan terhadap perubahan peningkatan pengetahuan. Dengan adanya pengetahuan yang baik akan mempengaruhi sikap seseorang khususnya bagi penderita DM. pengetahuan ini akan membawa penderita DM untuk menentukan sikap. Oleh karena itu Penggunaan media booklet merupakan salah satu alternatif untuk mengatasi kelemahan yang ada pada leaflet. Tujuan penelitian adalah untuk mengetahui pengaruh pemberian konseling dengan media booklet terhadap pengetahuan dan sikap penderita DM. Metode penelitian merupakan jenis penelitian quasi eksperimen dengan menggunakan rancangan pre test-post test with control group. Penelitian ini dilakukan pada bulan Februari – Mei 2022. Populasi penelitian ini yaitu seluruh pasien DM rawat inap di RSUD Penembahan Senopati Bantul. Pengambilan sampel dengan purposive sampling, yaitu masing- masing 28 responden untuk kelompok booklet dan leaflet dan variabel terikat yaitu pengatuahn dan sikap pasien DM. Analisis data shapiro Wilk, wilcoxon, dan Mann Whitney. Hasil penelitian menunjukkan adanya perbedaan responden sebelum dan sesudah diberikan konseling gizi dengan media booklet dan leaflet terdapat peningkatan pengetahuan dan sikap yang signifikan yaitu pengetahuan pada kelompok booklet (p=0,001), sikap (p=0,000), serta pengetahuan pada kelompok leaflet (p=0,017) dan sikap (p=0,005). Booklet lebih efektif untuk meningkatkan pengetahuan (p=0,017) dan sikap (p=0,05) pasien DM dibanding dengan penggunaan media leaflet. Kesimpulan penelitian adalah penggunaan media booklet lebih efektif dibandingan dengan penggunaan media leaflet.